VASCULOGENESIS IN VON HIPPEL-LINDAU DISEASE ASSOCIATED TUMORS - Lonser, Russell R. (Oxford University Press, 2014)
BACKGROUND: Emerging data indicate that von Hippel-Lindau disease (VHL) associated tumors arise from embryologic hemangioblasts that can form vessels (endothelial cells) and blood cells. Nevertheless, the origin of VHL-associated vasculature is not known. To determine the origin of VHL-associated tumor vasculature, we investigated the neoplastic vasculature from VHL patients. METHODS: Microdissected VHL-associated tumor (compared to control non-VHL tissues) vascular features were examined using immunohistochemical staining for CA9, HIF-2a, HIF-1a, CD31 and Factor VIIIa. Origin of tumor vascular elements (tumor versus non-tumor) was assessed by LOH and FISH analysis. Intratumoral vasculogenesis was assessed in vivo using the VHL-deficient UMRC6 renal carcinoma murine xenograft model. RESULTS: We demonstrate that isolated vascular structures and blood vessels within VHL-associated neoplasms (including hemangioblastomas, renal cell carcinoma and pancreatic tumors) are a result of tumor-derived vasculogenesis. Further, similar to hemangioblastomas, other VHL-associated neoplasms possess vascular tissue of tumor origin. Similarly, tumor-derived endothelial cells emerge within implanted VHL deficient UMRC6 renal cell carcinoma murine xenografts. CONCLUSIONS: These findings further establish the embryologic, developmentally arrested, hemangioblast as the tumor cell of origin for VHL-associated hemangioblastomas and indicate that it is also the progenitor cell for other VHL-associated tumors. SECONDARY CATEGORY: Neuropathology & Tumor Biomarkers.